2006
DOI: 10.1094/mpmi-19-0062
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Flower Abnormalities Induced by Stolbur Phytoplasma Infection Are Associated with Changes of Expression of Floral Development Genes

Abstract: Tomato (Lycopersicon esculentum cv. Micro-Tom) plants infected by the stolbur phytoplasma (isolate PO) display floral abnormalities, including sepal hypertrophy, virescence, phyllody, and aborted reproductive organs, which are reminiscent of those observed in Arabidopsis thaliana mutants affected in flower development genes. Semiquantitative reverse transcription-polymerase chain reaction and in situ RNA hybridization were used to compare expressions of meristem and flower development genes in healthy and stol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
66
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 41 publications
3
66
0
1
Order By: Relevance
“…Although we were unable to identify SAP54 homologs in a number of phytoplasmas known to influence flower architecture (e.g. stolbur phytoplasma; Pracros et al, 2006), our efforts were severely constrained by the limited availability of phytoplasma sequence data; thus, it cannot be concluded that these phytoplasmas do not encode a SAP54-like effector. Conversely, it is possible that these phytoplasmas employ different effectors to modulate flower development in their hosts.…”
Section: Phloem-expressed Sap54 Alters Floral Organ Identitymentioning
confidence: 98%
See 2 more Smart Citations
“…Although we were unable to identify SAP54 homologs in a number of phytoplasmas known to influence flower architecture (e.g. stolbur phytoplasma; Pracros et al, 2006), our efforts were severely constrained by the limited availability of phytoplasma sequence data; thus, it cannot be concluded that these phytoplasmas do not encode a SAP54-like effector. Conversely, it is possible that these phytoplasmas employ different effectors to modulate flower development in their hosts.…”
Section: Phloem-expressed Sap54 Alters Floral Organ Identitymentioning
confidence: 98%
“…For example, the production of a secondary flower in place of a carpel (loss of fourth whorl determinacy) indicates that phytoplasmas might interfere in some way with the function of the C-class protein AGAMOUS, and there is evidence that the expression of an AGAMOUS ortholog is altered in tomato (Solanum lycopersicum) infected with stolbur phytoplasma (Pracros et al, 2006). We also notice striking similarities between flowers of AY-WB-infected plants and sep1 sep2 sep3/+ sep4 quadruple mutants (Ditta et al, 2004).…”
Section: Phloem-expressed Sap54 Alters Floral Organ Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…By the same techinque, Carginale et al (2004) found only four genes that were differentially expressed in Prunus armeniaca infected by phytoplasma. Using semi-quantitative RT-PCR and in situ RNA hybridization, Pracros et al (2006) found some floral development genes to be differentially regulated in a tomato-stolbur phytoplasma interaction.…”
mentioning
confidence: 99%
“…Plants with phytoplasmal diseases often exhibit symptoms of shoot proliferation, witches'-broom (WB) growth, and flower malformation (13). Studies have revealed that, in deformed flowers of phytoplasma-affected plants, expressions of FM and floral organ identity genes become altered (14)(15)(16)(17) (Table 1). Although such findings provided some insights into molecular events involved in homeotic transformations of floral organs, the underlying response mechanisms that led to phytoplasma-induced multiple morphological abnormalities have remained unexplored.…”
mentioning
confidence: 99%